Overcoming the environmental crisis in the forestry sector of Ukraine in the context of the ecocentric paradigm - Gulac, Оlena; Oleksenko, Roman; Kaluha, Volodymyr; Kravchenko, Olena; Yukhymenko, Nataliia (Journal of the University of Zulia, 2022)
The purpose of the scientific research is to determine and justify the need to harmonize the environmental legislation of Ukraine and the EU in the field of forest resources, based on the prism of the "ecocentric paradigm and a new worldview". To achieve this goal, general scientific and special scientific methods of cognition were used, in particular dialectical, formal-logical, analysis and synthesis, system-structural, comparative-legal, formal-legal, predictive. The author substantiates the creation of an environmental strategy of Ukraine, which would be based on the principles of sustainable development, based on the need for greening forest management, among other things. It is noted that the harmonization of the legislation of Ukraine and the EU is aimed at implementing legal guarantees for the comprehensive application of the principle of mutual benefit and the principle of environmental cooperation in order to liberalize economic relations between Ukraine and its neighbors, on the one hand, and prevent environmental damage, on the other. It is proposed to introduce a whole range of measures, starting from the highest state level, aimed at increasing the level of greening the nature management of forest resources.